The Relationship between Parents' Knowledge of Dental and Oral Health and the Incidence of Dental Caries in Nurul Hayat Islamic Kindergarten School Children in Kapuk Village, Cengkareng District North Jakarta - Syarina Ria; Olivia Nency (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background Parents, especially mothers, have an important role in developing children's positive behavior towards dental and oral health. Parents' participation in maintaining children's dental and oral health can be implemented by paying attention to children's behavior regarding dental and oral health and children's eating patterns. Writing Objective: to determine the relationship of knowledge about oral and dental health with the incidence of dental caries in Islamic Kindergarten students at Nuruk Hayat, Kapuk Village, Cengkareng District, North Jakarta. Research Methods: The sample size in this study used a total side of 50 students of Nurul Hayat Islamic Kindergarten in Kapuk Village, Cengkareng District, North Jakarta. This study was to determine parents' knowledge about dental and oral health using a questionnaire conducted by interviewing parents and children of Nurul Hayat Islamic Kindergarten in Kapuk Village, Cengkareng District, North Jakarta. The data analysis used was univariate and bivariate analysis using the chi square test. Research Results The results showed that parents' knowledge of dental and oral health on the incidence of caries on the Chy-square test resulted in a P value of 0.00 <0.05, so the analysis was that there was a relationship between the history of parental knowledge about dental and oral health and the incidence of caries. The results of the OR calculation were 0.583, which means that the incidence of caries was 0.583 times lower with good parental knowledge about dental and oral health compared to parents with less knowledge (95% CI 0.362-0.941). Conclusions and Suggestions: It is hoped that the results of this study can be used as a reference for students about providing education to parents and children about oral and dental health.